Authorial photography as a translation of memories and subjective affections in shared dialogues in educational activities in the cultural space (Revista Apotheke, 2020)
This article deals with the teaching and production of artistic photography in the state ofParaíba. Having as a cut the FIC extension course in artistic photography from the FederalInstitute of Education, Science and Technology of Paraíba – IFPB. Such improvement is offeredfree of charge, providing access to a diverse audience. The methodology used was a casestudy with participant research. The text explains about the current time, without losing sightof the historicity of teaching, learning and fluidity of contemporary art in Paraíba, with a focuson teaching and production of artistic photography.
Keywords: artistic photography; visual art; extesion courses; photography teaching